Altered functional network topology properties to detect anxiety and depression caused by Crohn’s disease and disease severity - Jiaxing Yang; Kechen Yue; Jingwen Sun; Changjie Pan; Xintong Wu; Yongjun Cheng; Xiaomeng Wu; Haifeng Shi (Brain Research Bulletin)
Objective: Here we investigated changes in topological properties of functional brain networks among individuals with Crohn’s disease (CD) and to determine whether these changes are related to CD severity, as well as CD-associated anxiety and depression, which are regulated by the brain–gut axis mechanism. Methods: In total, 31 individuals with CD, 21 with irritable bowel syndrome (IBS), and 20 healthy controls underwent functional magnetic resonance imaging. Individuals with CD or IBS were also evaluated using the Hospital Anxiety and Depression Scale-Anxiety (HADS-A) and Depression (HADS-D) scales, as well as the simple endoscopic score for CD (SES-CD). Graph theory-based methods were applied to calculate the topological properties of brain networks, and comparisons among the three groups were performed using one-way analysis of variance. Partial correlation analysis was used to assess correlations among these properties and HADS-A, HADS-D, and SES-CD scores. Results: In the CD group, altered global topological properties were identiﬁed, and altered local topological properties were observed in 13 brain regions. The functional connectivity (FC) between the default mode network and visual network was increased, and the FC in the limbic system was decreased. In the CD group, local topological properties in the amygdala and precuneus were negatively correlated with HADS-A scores, and local topological properties in the superior occipital gyrus were positively correlated with SES-CD scores. Conclusion: Both global and regional topologies of brain networks were impaired in individuals with CD, which were correlated with clinical scores, suggesting that these values could serve as neuroimaging metrics reflecting the degree of anxiety caused by CD and CD severity.